Comments on "A robust color image watermarking with singular value decomposition method". (March 2016) - Loukhaoukha, Khaled; Refaey, Ahmed; Zebbiche, Khalil
Abstract: In the paper entitled "A robust color image watermarking with singular value decomposition method" (Dogan et al., 2011), a robust digital image watermarking algorithm based on singular value decomposition for multi-modal biometric color face and iris images has been proposed. This comment shows that this proposed method has some defects and limits, and consequently, it cannot be used to secure multi-modal biometric systems.